Microbial diversity and ecology of geothermal springs in the high-grade metamorphic terrain of Sri Lanka - Rupasinghe R; Amarasena S; Wickramarathna S; Biggs PJ; Chandrajith R; Wickramasinghe S (Elsevier Ltd, 2022)
The current study evaluated the bacterial diversity of six hot water spring clusters in Sri Lanka by Illumina MiSeq sequencing of the V3–V4 region of the 16S rRNA gene. Bacterial abundance measures and diversity statistics were assessed using QIIME2 metagenomics workflow, and the results were compared according to the region, the water temperature at the surface (36–59 °C), and pH (6.25–8.35). The predominant phyla observed were Proteobacteria, Actinobacteria, Firmicutes, [Thermi], and Cyanobacteria. A low abundance of Bacteroidetes, Chloroflexi, Acidobacteria, TM7, and Spirochaetes was detected in most of the springs. Several important bacterial species such as Deinococcus geothermalis that can tolerate Martian-like conditions, genera such as Legionella and Campylobacter that contain pathogenic species, sulfur metabolizing Desulfovibrio, Desulfatirhabdium, Desulforhabdus, Desulfacinum, Thermodesulfovibrio, Desulfovirga, and Thiobacter species, and several other species with the potential practical industrial application were detected. Several opportunistic human pathogens were detected in the water samples and raised a public health concern about the management of post-bathing water. Based on the Bray Curtis beta diversity metric, the microbial distribution correlated with temperature rather than the geographic distance. This study provides valuable new insights into the bacterial diversity of the hot springs in Sri Lanka. Future research needs to be conducted on industrially important thermophiles identified in this study.
Keywords: Bacterial abundance; Ecological diversity; Geothermal ecosystems; Extreme environments1; 16S rRNA amplicon sequencing